Sociodemographic Risk, Parenting, and Effortful Control: Relations to Salivary Alpha-amylase and Cortisol in Early Childhood - Taylor, Zoe E. (2012)
Early sociodemographic risk, parenting, and temperament were examined as predictors of the activity of children’s (N = 148; 81 boys, 67 girls) hypothalamic-pituitary-adrenal axis and autonomic nervous system. Demographic risk was assessed at 18 months (T1), intrusive-overcontrolling parenting and effortful control were assessed at 30 months (T2), and salivary cortisol and alpha-amylase were collected at 72 (T3) months of age. Demographic risk at T1 predicted lower levels of children’s effortful control and higher levels of mothers’ intrusive-overcontrolling parenting at T2. Intrusive-overcontrolling parenting at T2 predicted higher levels of children’s cortisol and alpha-amylase at T3, but effortful control did not uniquely predict children’s cortisol or alpha-amylase. Findings support the open nature of stress responsive physiological systems to influence by features of the early caregiving environment and underscore the utility of including measures of these systems in prevention trials designed to influence child outcomes by modifying parenting behavior.